An aluminum nitride photoconductor for X-ray detection - 王新建 宋航 李志明 蒋红 黎大兵 缪国庆 陈一仁 孙晓娟 (Journal of semiconductors, 2012)
An AlN photoconductor for X-ray detection has been fabricated,and its response to X-ray irradiation intensity is studied.The photoconductor has a very low leakage current,less than 0.1 nA at an applied voltage of 100 V in the absence of X-ray irradiation.The photocurrent measurement results clearly reveal that the photocurrent is proportional to the square root of the X-ray irradiation intensity,and under relatively high irradiation the photocurrent can reach values one order of magnitude larger than the dark current when a voltage of 100 V is applied across the AlN photoconductor.By using the ABC model the dependence of the photocurrent on the X-ray irradiation intensity is analyzed,and a reasonable interpretation of the physical mechanism is obtained.